Safinatu Al-Ghulam: Meningkatkan motivasi kerja di kalangan generasi muda - Khairia, Najwa; Adawiyah, Rabiatun (Maliki Interdisciplinary Journal, 2024)
Work motivation is an important factor in determining individual success and productivity. Currently, millennials and generation Z face unique challenges that require an innovative and passionate approach to work. The book "Safinatu al-Ghulam" by Sheikh Muhammad Azhari bin Ma’ruf al-Khatib al-Palimbani is a guide that has the potential to increase work motivation among the younger generation. This research aims to explore the guidelines in Safinatu al-Ghulam which can influence the motivation and performance of the younger generation. A qualitative approach was used in this research by analyzing the manuscript text and then recording the important points in it. Through this in-depth analysis, this research identifies core values ​​in the book Safinatu al-Ghulam that can inspire the younger generation, such as perseverance and tenacity in achieving goals. The research results show that Safinatu al-Ghulam contains guidelines that can increase motivation at work. These findings indicate that the Safinatu al-Ghulam book can be an effective tool for increasing work motivation among the younger generation.